Praktik Resiprositas dalam Tradisi Rewang di Desa Banglas Kecamatan Tebing Tinggi Kabupaten Kepulauan Meranti - Ahmad Affandi; Rina Susanti (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the practice of reciprocity within the persatuan barang (goods-sharing) group during the implementation of the rewang tradition in Desa Banglas, Kecamatan Tebing Tinggi, Kabupaten Kepulauan Meranti. The main focus of the research is to identify the various forms of exchange that occur, whether in the form of money, goods, or labor. A narrative qualitative approach was used, with data collected through in-depth interviews, non-participant observation, archival review, and documentation of bookkeeping records. The subjects of this research are members of the persatuan barang group who actively participate in social and cultural events in the village. The findings reveal three types of reciprocity: generalized, balanced, and negative. Generalized reciprocity is evident in voluntary contributions without expecting immediate return, often practiced among close kin or neighbors. Balanced reciprocity is demonstrated through exchanges of equal value with a certain expectation of timely return, particularly during communal events like weddings or funerals. Negative reciprocity, although rare, involves unequal exchanges that may lead to social tensions or perceptions of unfairness. These findings indicate that the persatuan barang group functions not only as an informal economic mechanism but also as a cultural institution that fosters mutual assistance, reinforces social cohesion, and preserves traditional values. The exchange systems operate within an implicit moral economy that prioritizes collective welfare over individual gain. Additionally, the tradition of rewang and the organizational role of persatuan barang highlight the resilience and adaptability of indigenous practices in supporting rural livelihoods amid changing socioeconomic conditions. The study suggests that such local systems of reciprocity play a vital role in sustaining social capital, strengthening community identity, and ensuring social security in the absence of formal welfare structures. Further research is recommended to explore the long-term impact of these practices on community resilience and rural development.